Research on the impact of TPR teaching method on international children’s Chinese learning in a cross-cultural environment - Zhang , Xi; Sheng, Yiyuan (Journal of Roi Kaensarn Academi, 2024)
This study aims to study the influence of Total Physical Response (TPR) teaching on Chinese learning in an intercultural context. By combining literature review, case analysis and field investigation, we are committed to providing a comprehensive understanding of the practical application of TPR pedagogy in Chinese teaching and its potential effects on infant language acquisition in an international context. The research approach include collecting and analyzing the learning experiences of international young children from diverse cultural backgrounds. We will focus on how TPR teaching method promotes Chinese vocabulary accumulation and grammar understanding by combining body movements and language. In addition, we will gain insight into the challenges and advantages of adopting the TPR pedagogy through faculty and parent interviews in intercultural education. Through this study, we not only expect to provide new theoretical perspectives for the field of cross-cultural language education, but also provide practical teaching strategies for the international preschool teaching of Chinese as a second language. The results of the study will facilitate a better understanding of the applicability of TPR pedagogy in different cultural contexts and provide a useful reference for language education practice and policy making. Finally, by deeply studying the role of TPR teaching method in international Chinese learning for young children, this study aims to provide new insights and inspirations for language education in the context of globalization.